SOCIO-ECOLOGICAL-HEALTH STUDY IN IRAN: Life Sciences-Health - Mousavi Davoudi, Dr.Seyed Mehdi (International Journal of Life Science and Pharma Research, 2016)
Development of the society, health and ecology are dependent on each other in all the countries including developed or developing countries like Iran. The influence of the society on health and life style is enormous. It also influences the development of the child, which inturn produces an untoward impact on the marital relationship of parents. Ecological factors also produce both good and adverse impact on the health of human. Presence of nonbiodegradable heavy metals in the soil causes untoward conditions to the ecological system as well as to the human of that society. In Iran, the presence of date palm tree can reduce the heavy metal content of the soil, has been reported by many researchers. As per many studies, the adverse environmental conditions as well as the human diseases like AIDS, cancer and many other psychological disorders may pull back the development of the society of Iran. Moreover, the Law of Iran also plays an important role in the society, which must be bit strict in regulation of spreading diseases like HIV infection and adverse health conditions due to untoward ecological effects on human health. The research findings in this special issue focuses on these issues and would believe that these would address those issues for betterment of the society.